Photocarrier transport and carrier recombination efficiency in vertically aligned nanowire arrays synthesized via metal-assisted chemical etching - Muldera, Joselito E. (Animo Repository, 2013)
The carrier dynamics and recombination characteristics of vertically aligned silicon nanowires are investigated using terahertz emission and photoluminescence spectroscopy, respectively. It is observed that the presence of pores on the walls in two-step-synthesized silicon nanowires greatly affects the carrier dynamics, compared with nanowires synthesized using a one-step process. These pores become efficient carrier recombination sites wherein carriers are collected upon photoexcitation. Additionally, pores effectively diminish the surface electric field thereby inhibiting the terahertz emission. Finally, nanowire-length-dependent terahertz emission is observed only for the one-step-synthesized nanowires whereas the two-step-synthesized nanowire samples exhibited length dependence of their photoluminescence intensity.